Pengaruh Perluasan Bukaan Pit Terhadap Sistem Penyaliran Tambang Di Pit 19A Blok Timur Tahun 2023 PT Indominco Mandiri, Kutai Timur,Kalimantan Timur - Rachma, Annisya Aulia (ReTII, 2023)
PT Indominco Mandiri is a company engaged in coal mining, which is located in Teluk Pandan, East Kutai, East Kalimantan. The main activities of mining, consist of stripping overburden, disclosure, loading and carrying coal from the pit to the Coal Crushing Plant. The mining system used is an open mine using the strip mine method. Therefore, the activities are greatly impacted by weather, including rainfall. In 2023, the pit will be expanded so the water discharge that entering the pit will be increase. With huge water discharge, a larger mine drainage capacity is also needed. Therefore, it is necessary to calculate the capacity of a good mine drainage system. Based on calculations and analysis of rainfall data for 2013-2022 using the Gumbell method, the planned rainfall was 112.85 mm with a return period of rain 5 years and a hydrological risk 85.6%. The Mononobe formula was used to calculate rainfall intensity and obtained rate at 17,15 mm/day which is included in heavy rain. The research location is divided into 4 rain catchment areas, 3 areas are inside the pit while an area is outside the pit. The area of ​​rain catchment area I is 79.5 Ha with a runoff water discharge is 2.82 m3/second, rain catchment area II is 76.3 Ha with runoff water discharge is 2.70 m3/second, rain catchment area III is 112 ha, 4 Ha with a runoff water discharge is 3.98 m3/second, rain catchment area IV covering an area of ​​51.8 Ha with a runoff water discharge is 0.98 m3/second. Based on the research results, there are 2 open channels, open channel I drains runoff water outside the pit and open channel II flows water pumped from the sump to the settling pond. The sump that needs repair is the southern sump with a recommended volume is 13,621 m3 with 2 Multiflo 420 EX pumps with a pumping flow of 1000 m3/hour. The settling pond consists of 7 compartments, dredging of each compartment must be carried out regularly so that the settling pond can accommodate the pumping discharge. Therefore exist of expansion pit, capacity or size of open channels and settling pond isn’t required additional capacity, but for sump capacity and the RPM and debit of pump used in the south sump need to be repaired.